The Implementation of School Financial Management System in Managing the BOS Fund - Santosa, Sedya; Mihrajuddin, andi; Munastiwi, Erni (Universitas Islam Negeri Raden Intan Lampung, 2022)
School financial management should be managed properly. With clear and transparent financial management, it will affect operational systems and mechanisms to meet the various elementary needs of the school. Financial management also plays a determinant role for the success of education. Thus, financial management needs to be implemented by educational institutions, so that the use of school funds can be more effective and efficient and the budget misuse is able to be minimized appropriately. This study aims to find out how the education financial management system is implemented in managing BOS funds. In this study, the authors used a qualitative approach with the type of field research conducted at SMAN 17 Bombana, Southeast Sulawesi Province. The data from this study were obtained from observations, interviews and documentations. As reseach participants, this study involved the head of school, treasurer of school, committee chairs, student guardians, educators and education staffs. Then, data were analyzed and conclusions were drawn. Therefore, this study shows that the implementation of the education financial management system in managing BOS funds at SMAN 17 Bombana, Southeast Sulawesi Province has been implemented very well. This is evidenced by the steps carried out, including financial planning by holding meetings first, then financial implementation which is divided into three parts, namely acceptance, distribution and management. Another indicator is the evaluation system which is divided into two parts, consisting of the school's internal side and the education office's external side.